657. Genomic Insights into Virulence Factors Affecting a Tissue-invasive Klebsiella pneumoniae Infection. (4th December 2021) - Matono, Takashi; Morita, Masatomo; Nakao, Nodoka; Teshima, Yuji; Yamate, Ryosuke; Hijikata, Takamichi; Hoashi, Kosuke; Ohashi, Yusuke; Hasegawa, Yuichi; Okinaka, Tomohide; Ohnishi, Makoto
Abstract: Background: Japan is one of the hypervirulent Klebsiella pneumoniae (hvKp) endemic areas, resulting in an alarming issue in actual clinical settings. However, little is known regarding key virulence factors responsible for hvKp infection. Methods: We analyzed K. pneumoniae isolates collected between 2017 and 2019, and defined hvKp as a pyogenic infection. Classical K. pneumoniae (cKp) involved a non-invasive infection or uncomplicated bacteremia. Isolates belonging to the K. pneumoniae species complex were excluded. Results: We analyzed 112 isolates, including 19 hvKp, 67 cKp, and 26 colonizers, by whole-genome sequencing. Population genomics revealed that the K1-sequence type (ST) 82 clade was distinct from that of K1-ST23 clone (Figure 1). The virulence-gene profiles also differed between K1-ST82 (aerobactin and rmpA ) and K1-ST23 (aerobactin, yersiniabactin, salmochelin, colibactin, and rmpA / rmpA2 ). The K2 genotype was more diverse than that of K1. A neighboring subclade of K1-ST23 (comprising ST29, ST412, ST36, and ST268) showed multidrug-resistance and hypervirulence potentials. Logistic-regression analysis revealed that diabetes mellitus was associated with K. pneumoniae infection (odds ratio [OR]: 4.11; 95% confidence interval [CI]: 1.14–14.8). No significant association was found between hvKp diagnosis and clinical characteristics, such as diabetes mellitus or community acquisition (Table 1). The K1 genotype (OR: 9.02; 95% CI: 2.49–32.7; positive-likelihood ratio [LR]: 4.08), rmpA (OR: 8.26; 95% CI: 1.77–38.5; positive LR: 5.83), and aerobactin (OR: 4.59; 95% CI: 1.22–17.2; positive LR: 3.49) were substantial diagnostic predictors of hvKp (Table 2). Figure 1. Phylogenetic distribution of genetic virulence factors in 112 K. pneumoniae isolates The highlighted strains are clinically pathogenic (orange, hypervirulent K. pneumoniae ; yellow, classical K. pneumoniae ; sky blue, colonization). The non-highlighted strain (NTUH-K2044) is a reference K. pneumoniae strain. Conclusion: In hvKp-rich settings, diabetes mellitus, community-acquisition, and siderophores other than aerobactin were not remarkable predictors of hvKp infection. However, the K1 genotype, rmpA, and aerobactin were found to be substantial predictors, warranting clinical assessment of any possible/further pyogenic (metastatic) infection. We believe that these findings shed light on key hvKp virulence factors. Disclosures: All Authors : No reported disclosures